The novel pyrrolo-1,5-benzoxazepine, PBOX-6, synergistically enhances the apoptotic effects of carboplatin in drug sensitive and multidrug resistant neuroblastoma cells - Lennon, Jennifer C.; Bright, Sandra A.; Carroll, Eilis; Butini, Stefania; Campiani, Giuseppe; O’Meara, Anne; Williams, D. Clive; Zisterer, Daniela M. (Biochemical pharmacology, 2014)
Neuroblastoma, a malignancy of neuroectoderrmal origin, accounts for 15% of childhood cancer deaths. Despite advances in understanding the biology, it remains one of the most difficult paediatric cancers to treat. A major obstacle in the effective treatment of neuroblastoma is the development of multidrug resistance (MDR). There is thus a compelling demand for new treatment strategies for this cancer that can bypass such resistance mechanisms. The pyrrolo-1,5-benzoxazepine (PBOX) compounds are a series of novel microtubule-targeting agents that potently induce apoptosis in various cancer cell lines, ex vivo patient samples and in vivo cancer models. In this study we examined the ability of two members, PBOX-6 and -15, to exhibit anti-cancer effects in a panel of drug sensitive and MDR neuroblastoma cell lines. The PBOX compounds potently reduced the viability of all neuroblastoma cells examined and exhibited a lower fold resistance in MDR cells when compared to standard chemotherapeutics. In addition, the PBOX compounds synergistically enhanced apoptosis induced by etoposide, carboplatin and doxorubicin. Exposure of drug sensitive and resistant cell lines to PBOX-6/carboplatin induced cleavage of Bcl-2, a downregulation of Mcl-1 and a concomitant increase in Bak. Furthermore, activation of caspase-3, -8 and -9 was demonstrated. Finally, gene silencing of Mcl-1 by siRNA was shown to sensitise both drug sensitive and multidrug resistant cells to carboplatin-induced apoptosis demonstrating the importance of Mcl-1 downregulation in the apoptotic pathway mediated by the PBOX compounds in neuroblastoma. In conclusion, our findings indicate the potential of the PBOX compounds in enhancing chemosensitivity in neuroblastoma.